Peningkatan Kompetensi Guru Dan Membangun Budaya Belajar Berkelanjutan Melalui Pembentukan Komunitas Belajar - Suesthi Rahayuningsih; Asih Andriyati Mardliyah; Achmad Rijanto (CV. Multi Kreasi Media, 2023)
The Community Partnership Empowerment Partner (PKM) was SMP Negeri 2 Kemlagi. The school was located on the outskirts of Mojokerto district and was founded in 2021. The problem faced by partners was the lack of knowledge about Learning Communities, especially about the process of forming and optimizing Learning Communities in schools. The aim of this PKM was to increase knowledge about Learning Communities, especially regarding the formation and optimization of Learning Communities to improve teacher competence, especially regarding character education and school culture. The method used was training in the form of workshops to facilitate the formation of learning communities and their optimization in partner schools to increase teacher competency by sharing knowledge and discussions related to character education and school culture. The results achieved after implementing PKM were that partners know about the importance of learning communities in schools, especially about the process of forming and optimizing learning communities in schools in an effort to improve teacher competency and learning culture in schools, with a participant attendance rate of 100% and a level of understanding of participant knowledge of 76% of the material provided.